If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 8 = 7a + -24 Reorder the terms: 8 + 3a = 7a + -24 Reorder the terms: 8 + 3a = -24 + 7a Solving 8 + 3a = -24 + 7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7a' to each side of the equation. 8 + 3a + -7a = -24 + 7a + -7a Combine like terms: 3a + -7a = -4a 8 + -4a = -24 + 7a + -7a Combine like terms: 7a + -7a = 0 8 + -4a = -24 + 0 8 + -4a = -24 Add '-8' to each side of the equation. 8 + -8 + -4a = -24 + -8 Combine like terms: 8 + -8 = 0 0 + -4a = -24 + -8 -4a = -24 + -8 Combine like terms: -24 + -8 = -32 -4a = -32 Divide each side by '-4'. a = 8 Simplifying a = 8
| 14=7-13+4a | | 6.5=5p | | X+0.25=10 | | 4(w+5)=6w+32 | | X-19.1=34.4 | | 12(3x+4)-5(2x-6)=6x-22 | | 4x-3x+10x=12 | | 4+8x=12+0 | | 6x=-7.8 | | -5-6b=7+7b+1 | | 6-x=7.8 | | ln(1+x^2)+x^1-7=0 | | -8-9x-4= | | 9y-7=10y | | 20+8(f-11)=-12 | | 24=2+4b | | 3x-16=3(x-6)+2 | | X+4.8=19 | | 2x+3=2.5x | | 7x-2=2x+43 | | 2x+18=2x | | 9r=5+10r | | 13x-2=13x-2 | | 3x(12x+x)=0 | | 2(5-m)=32 | | -2-4w=-5w-7 | | (2x-9)-(3x-3)=-(3x+3)-3x+9 | | 3=p*15 | | 6x+12y+15z= | | 11x+2=8x | | -9p=-10-10p | | t^2+16t+60= |